2020
DOI: 10.1371/journal.pone.0241415
|View full text |Cite
|
Sign up to set email alerts
|

The effect of air-pollution and weather exposure on mortality and hospital admission and implications for further research: A systematic scoping review

Abstract: Background Air-pollution and weather exposure beyond certain thresholds have serious effects on public health. Yet, there is lack of information on wider aspects including the role of some effect modifiers and the interaction between air-pollution and weather. This article aims at a comprehensive review and narrative summary of literature on the association of air-pollution and weather with mortality and hospital admissions; and to highlight literature gaps that require further research. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 122 publications
2
45
0
Order By: Relevance
“…An Italian study reported a linear correlation between high levels of NO 2 and PM 10 concentrations and the lack of possession of a home, low level of education, and population density [ 59 ]. Numerous studies have investigated the influence of SES on adverse health effects of air pollution, and there have been conflicting reports of effect modification [ 60 , 61 ]. This makes it difficult to draw a definitive conclusion on whether the short-term effects of air pollution on health are modified by SES.…”
Section: Discussionmentioning
confidence: 99%
“…An Italian study reported a linear correlation between high levels of NO 2 and PM 10 concentrations and the lack of possession of a home, low level of education, and population density [ 59 ]. Numerous studies have investigated the influence of SES on adverse health effects of air pollution, and there have been conflicting reports of effect modification [ 60 , 61 ]. This makes it difficult to draw a definitive conclusion on whether the short-term effects of air pollution on health are modified by SES.…”
Section: Discussionmentioning
confidence: 99%
“…The third explanation is related to experiential anxiety and worrying feelings about one’s physical health and future [ 27 ]. Through substantive research, people are made aware of the negative impact of air pollution on human’s physical health and the higher risk for acute and chronic diseases such as cardiovascular, respiratory, cancer and immune system diseases [ 8 , 9 , 28 ]. People living in highly polluted areas might experience stress and anxiety about physical illness, which is reflected in poorer mental well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Ambient air pollution is a mixture of particles (e.g., black carbon and particulate matter with diameters less than or equal to 10 μm: PM10 and to 2.5 μm: PM2.5) and gaseous chemicals (e.g., sulphur dioxide: SO 2 , nitrogen dioxide: NO 2 , carbon monoxide: CO, and ozone) that are released to the atmosphere from natural processes (e.g., windblown soil, volcano ashes, pollen, dust) or from man-made activities including energy production, livestock farming, traffic exhaust, and industrial and mining processes [ 8 , 9 ]. Inhalation of air pollutants can have major consequences on the human central nervous system and neuro-behavioural mechanisms [ 1 , 5 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Air pollution and temperature can be highly correlated [ 20 ] and are simultaneously exacerbated by climate change ( Figure 1 ) [ 21 ], although the correlation differs by pollutant. Air pollution may be a confounding factor for impacts of temperature on suicide and vice versa as both are associated with neuroinflammation in the brain and serotonin neurotransmission.…”
Section: Introductionmentioning
confidence: 99%